Selection of Reverse Logistics Activities Using an ANP-BOCR Model - Hernandez, C. T.; Marins, F. A. S. [UNESP]; Duran, J. A. R. (Ieee-inst Electrical Electronics Engineers Inc, 2016)
The Reverse Logistics (RL) activities are gaining importance in Brazilian companies. However, a relevant problem is to select RL activities using criteria of immediate and long-term effects for the organization. These situations can be treated as being Multi-Criteria Decision-Making (MCDM). In this work we adopted the Analytic Network Process (ANP) as the analytical technique of a MCDM problem that can be formulated when we have interest in to identify existing relationships between RL activities. The strategic criteria were included into the model to rate benefits (B), opportunities (O), cost (C) and risks (R). Here we present an analysis of sustainable practices identified in publishing companies, operating in Brazil. The results indicated that ANP-BOCR is an adequate method to select alternatives RL.
Keywords: Reverse Logistics; Multiple Criteria Decision Making; Analytic Network Process; BOCR